How Artificial Intelligence Brought a Paradigm Shift in the Digital Marketing Landscape: A Scientometric Mapping and Future Research Directions - Faruk, Mohammad; Islam, Md. Shahanur; Mondal, Depongker; Hossain, Md. Noyan; Tuhin, Md Rahat; Khatun, Mst. Eti; Ejarder, Sagor (International Review of Management and Marketing, 2025)
This bibliometric research aims to comprehensively analyze the application of Artificial Intelligence (AI) in digital marketing. The study uses the Scopus database to identify 355 research papers published between 2000 and 2025. This research intends to provide an overview of the research landscape, including the most cited articles, authors, and journals, to identify the trending topics of the research, and to determine the thematic development in this domain. The findings reveal that research in this field depicts exponential growth after 2017 and will continue to grow in the future and the Journal of Marketing is the most contributing journal. The most commonly used AI technologies in digital marketing include machine learning (ML), natural language processing (NLP), predictive modeling, and chatbots with tools such as ChatGPT, OptiMonkAI, Jasper, Midjourney, Manychat, Zapier, ElevenLabs, and OpusClip. The findings further synthesize that these AI tools and technologies enable marketers to collect and analyze large amounts of real-time data (structured, unstructured, and semi-structured) and are applied to achieve multifold strategic and tactical marketing objectives: to make improved customer segmentation, behavior prediction, and targeting, to enhance customer service, experience, and satisfaction, to ensure marketing efficiency through automation, to create and personalize content, and to efficiently manage social media and personalized email marketing and e-commerce website. However, there are concerns about the potential for the sustainable implication of AI considering data privacy and security and ethical issues. Future research should focus on the application of AI to ensure and enhance sustainable societal well-being (society 5.0) through marketing 5.0.